COMMUNICATION STRATEGY OF THE BAJENIS DISTRICT RELIGIOUS AFFAIRS OFFICE IN PROVIDING INFORMATION SERVICES TO THE COMMUNITY - Salsabillah Sinaga; Yusra Dewi Siregar (Journal Analytica Islamica, 2026)
This study aims to analyze the communication strategy implemented by the Bajenis District Religious Affairs Office (KUA) in delivering public service information to the public. Analyze the communication strategy of the Bajenis District Religious Affairs Office in delivering public service information, identify communication barriers faced by the Religious Affairs Office, analyze the efforts made by the Religious Affairs Office in overcoming these communication barriers. The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews and documentation. The results of the study indicate that the communication strategy of the Bajenis District KUA is carried out through face-to-face communication, utilization of print media, and optimization of digital media such as WhatsApp and social media. Communication barriers include differences in community literacy levels, limited human resources, and technical obstacles to digitizing services. Efforts made include simplifying messages, increasing the role of religious instructors, and adapting communication media based on community needs. A planned, participatory, and contextual communication strategy has been proven to increase the effectiveness of information delivery and the quality of public services.